Chronic noncommunicable diseases among college students: Simultaneity of risk behaviors - Vitória Barbosa da Costa; Lorena Ribeiro Soares dos Santos; Cristiane Feitosa Salviano; Andréia Guedes Oliva Fernandes (Revista Enfermagem Digital Cuidado e Promoção da Saúde)
OBJECTIVE: To identify the prevalence and simultaneity of risk factors for Chronic Noncommunicable Diseases (NCDs) among university students in the Federal District. METHOD: Cross-sectional study conducted in 2020 with 88 students from a private Higher Education Institution in the Federal District. Sociodemographic and risk factor variables for NCDs were analyzed. The outcome assessed was simultaneity of risk factors. RESULTS: A high prevalence of risk factors was observed, these being: inadequate eating habits, use of television, computer, tablet or cell phone, physical inactivity and family history of NCDs. The agglomeration of three or more risk factors was present in 47 (81.0%) students, with a predominance of females. CONCLUSION: The simultaneity of two or more risk factors in the university environment is common, with a high proportion among women, which may be due to social attributions.